A PERK–miR-211 axis suppresses circadian regulators and protein synthesis to promote cancer cell survival - Bu, Yiwen; Yoshida, Akihiro; Chitnis, Nilesh; Altman, Brian J.; Tameire, Feven; Oran, Amanda; Gennaro, Victoria; Armeson, Kent E.; McMahon, Steven B.; Wertheim, Gerald B.; Dang, Chi V.; Ruggero, Davide; et al. (Nature cell biology, 2018)
The unfolded protein response (UPR) is a stress-activated signalling pathway that regulates cell proliferation, metabolism and survival. The circadian clock coordinates metabolism and signal transduction with light/dark cycles. We explore how UPR signalling interfaces with the circadian clock. UPR activation induces a 10 h phase shift in circadian oscillations through induction of miR-211, a PERK-inducible microRNA that transiently suppresses both Bmal1 and Clock, core circadian regulators. Molecular investigation reveals that miR-211 directly regulates Bmal1 and Clock via distinct mechanisms. Suppression of Bmal1 and Clock has the anticipated impact on expression of select circadian genes, but we also find that repression of Bmal1 is essential for UPR-dependent inhibition of protein synthesis and cell adaptation to stresses that disrupt endoplasmic reticulum homeostasis. Our data demonstrate that c-Myc-dependent activation of the UPR inhibits Bmal1 in Burkitt’s lymphoma, thereby suppressing both circadian oscillation and ongoing protein synthesis to facilitate tumour progression. PERK regulates tumour cell survival. Bu et al. show that the unfolded protein response protein PERK induces miR-211 repression of the circadian factor Bmal1 to regulate protein synthesis and stress responses, contributing to tumour progression.